Joint Action of Azadirachta indica and Barringtonia asiatica Seed Extracts against Crocidolomia pavonana - Edy Syahputra; Minarti Minarti (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
A high population of Crocidolomia pavonana larvae reduces Brassicaceae crop productivity. To control the pest population, mixed plant extract as botanical insecticides is one of the alternatives. The purpose of this research is to evaluate the joint action between mixed extracts of Azadirachta indica and Barringtonia asiatica seed extracts against C. pavonana larvae and the effect on feeding behavior. The seeds are extracted with ethanol using the maceration method. Bioassays are conducted by a feeding method. Each level of concentration tested and controlled is repeated five times. The concentration-mortality relationship is analyzed using probit. Feeding behavior assayed by choice and no-choice at concentrations equivalent to LC25, LC50, and LC75. The results show the mixture of A. indica and B. asiatica seed extract at a ratio of 3:2.3 has a strongly synergistic action with an LC50 of 0.04% and a combination index of 0.27. The extract mixture at a concentration of 0.02-0.08% is reduced feeding activity 77.16-92.84%. Further research is needed to evaluate the extract mixture in the field.